Solid oxide electrolytic tank for electrolyzing carbon dioxide at high temperature and preparation method

By attaching La0.8Sr0.2Cr0.5Mn0.5O3 (LSCM) nanoparticles or CuO nanoparticles to the cathode material of the solid oxide electrolytic cell, the problem of poor catalytic performance of the cathode material is solved, and the electrolytic performance and CO2 reduction ability are significantly improved.

CN119710741AActive Publication Date: 2025-03-28ZHENGZHOU UNIV

Patent Information

Application Number
CN202411915995.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

In the prior art, the cathode material of solid oxide electrolytic cell (SOEC) has poor cathode performance, resulting in poor electrolytic performance.

Method used

La0.9Sr0.1Ga0.8Mg0.2O3 (LSGM) was used as the solid electrolyte substrate, Ce0.8Sm0.2O1.9 (SDC) was used as part of the isolation layer and anode material, and a composite composed of Sr2Fe1.5Mo0.5O6 (SFM) and SDC was used as the cathode material, and La0.8Sr0.2Cr0.5Mn0.5O3 (LSCM) nanoparticles or CuO nanoparticles were attached to the cathode material.

Benefits of technology

By attaching nanoparticles, the cathode material's oxygen storage capacity, carbon deposition resistance and CO2 reduction ability are improved, effectively reducing polarization resistance and improving the current density of electrochemical reduction of CO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710741A_ABST
    Figure CN119710741A_ABST
Patent Text Reader

Abstract

The invention discloses a solid oxide electrolytic tank for high-temperature electrolysis of carbon dioxide and a preparation method. The electrolytic tank comprises a solid electrolyte substrate, an isolation layer located on one side of the solid electrolyte substrate, a cathode located on the isolation layer and an anode located on the other side of the solid electrolyte substrate. And the material of the solid electrolyte substrate is La < 0.9 > Sr < 0.1 > Ga < 0.8 > Mg < 0.2 > O < 3 > (LSGM). And the material of the isolating layer is Ce < 0.8 > Sm < 0.2 > O < 1.9 > (SDC). The cathode material is a compound composed of Sr2Fe1. 5Mo0. 5O6 (SFM) and Ce0. 8Sm0. 2O1. 9 (SDC), and La0. 8Sr0. 2Cr0. 5Mn0. 5O3 (LSCM) nano particles or CuO nano particles are attached to the cathode material. The anode material is a compound composed of La < 0.7 > Sr < 0.3 > Co < 0.2 > Fe < 0.8 > O < 3 > (LSCF) and Ce < 0.8 > Sm < 0.2 > O < 1.9 > (SDC). The nanoparticles can effectively increase the specific surface area of an electrode, generate additional active sites, provide enough reaction interfaces and gas diffusion channels, effectively promote the reduction reaction of CO2, and contribute to reducing the local carbon concentration and reducing the occurrence rate of carbon deposition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid oxide electrolytic cells, and in particular to a solid oxide electrolytic cell for high-temperature electrolysis of carbon dioxide and a preparation method thereof. Background Art

[0002] Due to the extensive use of fossil fuels such as oil and natural gas, CO2 emissions have risen sharply. The emission of greenhouse gases (mainly CO2) has been considered the main factor causing global warming. Therefore, while developing clean and renewable energy, CO2 reduction or conversion technologies should be explored. Solid oxide electrolysis cell (SOEC) is one of the most promising technologies for high-temperature electrolysis of CO2 and has great commercial prospects. SOEC contains an electrolyte, an anode and a cathode. Driven by an external voltage, CO2 undergoes electrochemical dissociation on the cathode side to form CO and O 2- The produced CO can be used as valuable fuel or industrial raw material. 2- The electrons are transferred to the anode through the electrolyte, and eventually they lose electrons to generate oxygen. In SOEC, the CO2 reduction reaction at the cathode has a greater polarization loss than the oxygen evolution reaction at the anode, so the development and research of electrolytic cell materials mainly focuses on the optimization design of cathode structure and materials.

[0003] Nickel-yttrium-stabilized zirconia (Ni-YSZ) is widely used as a cathode material in solid oxide electrolytic cells (SOECs) due to its excellent electrocatalytic performance and low cost. However, carbon deposition easily occurs on Ni-YSZ, and Ni is easily oxidized during the redox process, resulting in poor electrolytic performance. Summary of the invention

[0004] The purpose of the present invention is to provide a solid oxide electrolytic cell for high-temperature electrolysis of carbon dioxide to solve the technical problem of poor catalytic performance of cathode materials in the prior art; at the same time, the purpose of the present invention is also to provide a method for preparing the above-mentioned solid oxide electrolytic cell.

[0005] To achieve the above-mentioned object, a solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide of the present invention adopts the following technical scheme: a solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide comprises a solid electrolyte substrate, an isolation layer located on one side of the solid electrolyte substrate, a cathode located on the isolation layer, and an anode located on the other side of the solid electrolyte substrate;

[0006] The solid electrolyte substrate material is La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O3(LSGM), isolation layer material is Ce 0.8 Sm 0.2 O 1.9(SDC), cathode material is Sr2Fe 1.5 Mo 0.5 O6(SFM) and Ce 0.8 Sm 0.2 O 1.9 (SDC) composed of a composite, and La is attached to the cathode material 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles or CuO nanoparticles; the anode material is La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) and Ce 0.8 Sm 0.2 O 1.9 (SDC) composed of a complex.

[0007] The CuO nanoparticles or La 0.8 Sr 0.2 Cr 0.5 Mn 0.5 The attachment amount of O3 (LSCM) nanoparticles is 2wt%-8wt% of the mass ratio of the nanoparticles to the cathode material.

[0008] A method for preparing a solid oxide electrolytic cell for high-temperature electrolysis of carbon dioxide comprises the following steps:

[0009] Ⅰ. Preparation of Sr2Fe 1.5 Mo 0.5 O6(SFM) powder, La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder;

[0010] II. preparing the powder in step I into cathode slurry, anode slurry and separator slurry;

[0011] III. Apply the isolation layer slurry in step II to one side of the solid electrolyte substrate by screen printing, dry and calcine to obtain an isolation layer; then apply the cathode slurry to the isolation layer by screen printing, and dry to form a cathode; then apply the anode slurry to the other side of the solid electrolyte substrate by screen printing, and dry to form an anode; finally, calcine to obtain a complete solid oxide electrolytic cell;

[0012] IV. The cathode of the solid oxide electrolytic cell in step III is subjected to an impregnation modification treatment to allow La to adhere to the cathode material. 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles or CuO nanoparticles.

[0013] In step Ⅰ, Sr2Fe 1.5 Mo 0.5 O6(SFM) powder was prepared by the following method:

[0014] 1) Sr(NO3)2, Fe(NO3)3·9H2O and (NH4)6Mo7O 24 4H2O is dissolved in deionized water as a raw material to form a nitrate solution;

[0015] 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, wherein the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5;

[0016] 3) adding an aqueous ammonia solution to the solution in step 2) to adjust the pH to 6-8;

[0017] 4) stirring the solution in step 3) in a heated water bath to obtain a wet gel;

[0018] 5) drying the wet gel to obtain a dry gel;

[0019] 6) Calcine the dry gel to obtain Sr2Fe 1.5 Mo 0.5 O6(SFM) powder.

[0020] In step Ⅰ, La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) powder was prepared by the following method:

[0021] 1) dissolving La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O and Co(NO3)2·6H2O as raw materials in deionized water to form a nitrate solution;

[0022] 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, wherein the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5;

[0023] 3) adding an aqueous ammonia solution to the solution in step 2) to adjust the pH to 6-8;

[0024] 4) stirring the solution in step 3) in a heated water bath to obtain a wet gel;

[0025] 5) drying the wet gel to obtain a dry gel;

[0026] 6) Calcine the dry gel to obtain La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) powder.

[0027] In step Ⅰ, Ce 0.8 Sm 0.2 O 1.9 (SDC) powder was prepared by the following method,

[0028] 1) dissolving Ce(NO3)3·6H2O and Sm(NO3)3·6H2O as raw materials in deionized water to form a nitrate solution;

[0029] 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, wherein the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5;

[0030] 3) adding an aqueous ammonia solution to the solution in step 2) to adjust the pH to 6-8;

[0031] 4) stirring the solution in step 3) in a heated water bath to obtain a wet gel;

[0032] 5) drying the wet gel to obtain a dry gel;

[0033] 6) Calcine the dry gel to obtain Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0034] SFM powder, SDC powder and pine oil are placed in a cup-shaped container in a mass ratio of 65:35:150, and ground until they are evenly mixed to form a viscous cathode slurry; LSCF powder, SDC powder and pine oil are placed in a cup-shaped container in a mass ratio of 65:35:150, and ground until they are evenly mixed to form a viscous anode slurry; SDC powder and pine oil are placed in a cup-shaped container in a mass ratio of 1:1.5, and ground until they are evenly mixed to form a viscous isolation layer slurry.

[0035] In step IV, the impregnation solution is prepared as follows,

[0036] Dissolve Cu(NO3)2·3H2O in anhydrous ethanol to prepare Cu(NO3)2·3H2O with a concentration of 0.1 mol·L -1 The first type of nitrate solution.

[0037] In step IV, the impregnation solution is prepared as follows,

[0038] 1) Dissolve La(NO3)3·6H2O, Sr(NO3)2, Cr(NO3)3·9H2O, and Mn(NO3)2 in anhydrous ethanol to form a nitrate solution.

[0039] 2) adding citrate and ethylenediaminetetraacetic acid to the above solution, with the molar ratio of total metal ions: ethylenediaminetetraacetic acid: citric acid being 1:1:1.5;

[0040] 3) The prepared solution was heated in a water bath and stirred, and ammonia water was added to control the pH value of the solution to 6-8 to prepare La 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) concentration is 0.1 mol·L -1 The second type of nitrate solution.

[0041] In step IV, the first type of nitrate solution or the second type of nitrate solution is dripped onto the cathode material, dried, and then calcined, so that CuO nanoparticles or La nanoparticles are attached to the cathode. 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles.

[0042] Beneficial effects of the present invention: La attached to the cathode material 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles or CuO nanoparticles have strong oxygen storage capacity (LSCM nanoparticles) and anti-carbon deposition ability as well as the ability to enhance CO2 reduction (CuO nanoparticles), which can effectively increase the current density of electrochemical reduction of CO2 and reduce polarization resistance. At the same time, these nanoparticles also effectively increase the specific surface area of ​​the electrode and produce additional active sites, provide sufficient reaction interface and gas diffusion channels, effectively promote the reduction reaction of CO2, help reduce local carbon concentration, and reduce the incidence of carbon deposition. Moreover, the production cost is low and the operation is simple and convenient. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a structural schematic diagram of a solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide according to the present invention;

[0044] Figure 2 The XRD patterns of the electrodes of SFM obtained in the comparative example and Cu-SFM and LSCM-SFM obtained in the experimental example 1 are shown;

[0045] Figure 3 Surface scanning electron micrographs of the electrodes of the SFM obtained in the comparative example and the Cu-SFM and LSCM-SFM obtained in the experimental example 1;

[0046] Figure 4 This is the impedance spectrum curve of a symmetrical battery in a CO2 atmosphere at 800°C;

[0047] Figure 5 The impedance spectrum curves of the SFM obtained in the comparative example and the Cu-SFM and LSCM-SFM obtained in the experimental example 1 when electrolyzing CO2 at 800°C and open circuit voltage (OCV);

[0048] Figure 6 It is the current density of the SFM obtained in the comparative example and the Cu-SFM and LSCM-SFM obtained in the experimental example 1 when electrolyzing CO2 at 800℃. DETAILED DESCRIPTION

[0049] A solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide according to the present invention, such as Figure 1 As shown, it includes a solid electrolyte substrate, an isolation layer located on one side of the solid electrolyte substrate, a cathode located on the isolation layer, and an anode located on the other side of the solid electrolyte substrate. The solid electrolyte substrate material is La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O3(LSGM). The isolation layer material is Ce 0.8 Sm 0.2 O 1.9 (SDC). The cathode material is Sr2Fe 1.5 Mo 0.5 O6(SFM) and Ce 0.8 Sm 0.2 O 1.9 (SDC) composed of a composite, and La is attached to the cathode material 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles or CuO nanoparticles. The anode material is La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) and Ce 0.8 Sm 0.2 O 1.9 (SDC) composed of a complex.

[0050] Among them, the above-mentioned La 0.8 Sr 0.2 Cr 0.5 Mn 0.5The attached amount of O3 (LSCM) nanoparticles or CuO nanoparticles is 2wt%-8wt% of the mass ratio of the nanoparticles to the cathode material.

[0051] The preparation method of the solid electrolyte reactor is described in detail below with reference to an embodiment:

[0052] Embodiment 1

[0053] Ⅰ. Preparation of Sr2Fe 1.5 Mo 0.5 O6(SFM) powder, La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0054] Sr2Fe 1.5 Mo 0.5 Preparation of O6(SFM) powder:

[0055] 1) Weigh Sr(NO3)2, Fe(NO3)3·9H2O and (NH4)6Mo7O in a certain stoichiometric ratio (molar ratio of 2:1.5:0.5). 24 4H2O was dissolved in deionized water.

[0056] 2) Adding citric acid and ethylenediaminetetraacetic acid to the uniformly dissolved solution, the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5.

[0057] 3) After the solution is evenly mixed, slowly add ammonia water to adjust the pH to 7 while stirring continuously.

[0058] 4) Then, a stirring bar was added to warm water at 80° C. and stirring was continued until a yellow-brown, viscous, transparent wet gel was formed.

[0059] 5) The obtained wet gel was quickly transferred to a cup-shaped container and dried in an oven at 160° C. for 7 h to obtain a porous dry gel.

[0060] 6) The dry gel was then transferred to a muffle furnace and calcined at 1050° C. for 5 h to obtain SFM powder.

[0061] La 0.7 Sr 0.3 Co 0.2 Fe 0.8 Preparation of O3(LSCF) powder:

[0062] 1) Weigh a certain stoichiometric ratio (molar ratio of 7:3:8:2) of La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O and Co(NO3)2·6H2O and dissolve them in deionized water.

[0063] 2) Adding citric acid and ethylenediaminetetraacetic acid to the uniformly dissolved solution, the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5.

[0064] 3) After the solution is evenly mixed, slowly add ammonia water to adjust the pH to 7 while stirring continuously.

[0065] 4) Then, a stirring bar was added to warm water at 80° C. and stirring was continued until a yellow-brown, viscous, transparent wet gel was formed.

[0066] 5) The obtained wet gel was quickly transferred to a cup-shaped container and dried in an oven at 160° C. for 7 h to obtain a porous dry gel.

[0067] 6) The dry gel was then transferred to a muffle furnace and calcined at 1050°C for 3 h to obtain LSCF powder.

[0068] Ce 0.8 Sm 0.2 O 1.9 (SDC) powder preparation:

[0069] 1) Weigh a certain stoichiometric ratio (molar ratio of 4:1) of Ce(NO3)3·6H2O and Sm(NO3)3·6H2O and dissolve them in deionized water.

[0070] 2) Adding citric acid and ethylenediaminetetraacetic acid to the uniformly dissolved solution, the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5.

[0071] 3) After the solution is evenly mixed, slowly add ammonia water to adjust the pH to 7 while stirring continuously.

[0072] 4) Then, a stirring bar was added to warm water at 80° C. and stirring was continued until a light yellow, viscous, transparent wet gel was formed.

[0073] 5) The obtained wet gel was quickly transferred to a cup-shaped container and dried in an oven at 180° C. for 12 h to obtain a porous dry gel.

[0074] 6) The dry gel was then transferred to a muffle furnace and calcined at 900°C for 3 h to obtain SDC powder.

[0075] Ⅱ. Prepare the powder in step Ⅰ into cathode slurry, anode slurry and isolation layer slurry.

[0076] Preparation of cathode slurry: SFM powder, SDC powder and pinene alcohol were placed in a small cup-shaped container at a mass ratio of 65:35:150 and ground for 1 h until they were evenly mixed to form a viscous electrode slurry.

[0077] Preparation of anode slurry: LSCF powder, SDC powder and pinene alcohol were placed in a small cup-shaped container at a mass ratio of 65:35:150 and ground for 1 h until they were evenly mixed to form a viscous electrode slurry.

[0078] Preparation of isolation layer slurry: SDC powder and pinene alcohol were placed in a small cup-shaped container at a mass ratio of 1:1.5, and ground for 1 hour until they were evenly mixed to form an isolation layer slurry with viscosity.

[0079] III. Apply the isolation layer slurry in step 2) on one side of the solid electrolyte substrate by screen printing, and obtain the isolation layer after drying and calcining; then apply the cathode slurry on the isolation layer by screen printing, and dry to obtain the cathode; then apply the anode slurry on the other side of the solid electrolyte substrate by screen printing, and dry to form the anode; finally, calcine to obtain a complete solid oxide electrolyte.

[0080] Among them, the preparation of the solid electrolyte substrate: LSGM powder (purchased directly) is dry-pressed into an electrolyte green body at a pressure of 200 MPa, and then calcined at 1400°C for 4 hours to obtain a solid electrolyte substrate.

[0081] Specifically, the isolation layer slurry is evenly applied on one side of the electrolyte substrate by screen printing, dried in an oven at 100°C, and transferred to a muffle furnace for calcination at 1200°C for 5h. Subsequently, the prepared cathode slurry is evenly applied on the same side of the electrolyte substrate by screen printing and dried in an oven at 100°C. Take it out, and evenly apply the prepared anode slurry on the other side of the electrolyte substrate by screen printing, and dry it in an oven at 100°C. Take it out, transfer it to a muffle furnace and calcine it at 1100°C for 2h to obtain a complete solid oxide electrolytic cell.

[0082] IV. The cathode of the solid oxide electrolyte in step III is subjected to an impregnation modification treatment so that La is attached to the base layer of the cathode. 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles or CuO nanoparticles.

[0083] Preparation of impregnation solution:

[0084] Type I nitrate solution:

[0085] Dissolve Cu(NO3)2·3H2O in anhydrous ethanol to prepare 0.1 mol·L -1 of nitrate solution.

[0086] Type II nitrate solution:

[0087] 1) La(NO3)3·6H2O, Sr(NO3)2, Cr(NO3)3·9H2O, and Mn(NO3)2 in a certain stoichiometric ratio (molar ratio of 8:2:5:5) were mixed into a nitrate solution;

[0088] 2) Citrate and ethylenediaminetetraacetic acid are added to the above solution, and the molar ratio of total metal ions: ethylenediaminetetraacetic acid: citric acid is 1:1:1.5.

[0089] 3) Stir the prepared solution in a water bath at 80°C and slowly add a certain amount of ammonia water while controlling the pH at 7 to prepare 0.1 mol·L -1 of nitrate solution.

[0090] Electrode modification: The first type of nitrate solution or the second type of nitrate solution was dripped on the cathode side of the solid oxide electrolytic cell with a pipette, dried in an oven at 80°C, and then the cell was calcined in a muffle furnace at 600°C for 2h to obtain a modified electrode with CuO nanoparticles or LSCM nanoparticles attached to the cathode. The attached CuO nanoparticles or LSCM nanoparticles accounted for 5wt% of the mass ratio of the cathode material. The electrodes impregnated with CuO and LSCM were named Cu-SFM and LSCM-SFM, respectively.

[0091] Embodiment 2

[0092] Ⅰ. Preparation of Sr2Fe 1.5 Mo 0.5 O6(SFM) powder, La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0093] Sr2Fe 1.5 Mo 0.5 Preparation of O6(SFM) powder:

[0094] 1) Weigh Sr(NO3)2, Fe(NO3)3·9H2O and (NH4)6Mo7O in a certain stoichiometric ratio (molar ratio of 2:1.5:0.5). 24 4H2O was dissolved in deionized water.

[0095] 2) Adding citric acid and ethylenediaminetetraacetic acid to the uniformly dissolved solution, the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5.

[0096] 3) After the solution is evenly mixed, slowly add ammonia water to adjust the pH to 6 while stirring continuously.

[0097] 4) Then, a stirring bar was added to warm water at 80° C. and stirring was continued until a yellow-brown, viscous, transparent wet gel was formed.

[0098] 5) The obtained wet gel was quickly transferred to a cup-shaped container and dried in an oven at 160° C. for 7 h to obtain a porous dry gel.

[0099] 6) The dry gel was then transferred to a muffle furnace and calcined at 1050° C. for 5 h to obtain SFM powder.

[0100] La 0.7 Sr 0.3 Co 0.2 Fe 0.8 Preparation of O3(LSCF) powder:

[0101] 1) Weigh a certain stoichiometric ratio (molar ratio of 7:3:8:2) of La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O and Co(NO3)2·6H2O and dissolve them in deionized water.

[0102] 2) Adding citric acid and ethylenediaminetetraacetic acid to the uniformly dissolved solution, the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5.

[0103] 3) After the solution is evenly mixed, slowly add ammonia water to adjust the pH to 6 while stirring continuously.

[0104] 4) Then, a stirring bar was added to warm water at 80° C. and stirring was continued until a yellow-brown, viscous, transparent wet gel was formed.

[0105] 5) The obtained wet gel was quickly transferred to a cup-shaped container and dried in an oven at 160° C. for 7 h to obtain a porous dry gel.

[0106] 6) The dry gel was then transferred to a muffle furnace and calcined at 1050°C for 3 h to obtain LSCF powder.

[0107] Ce 0.8 Sm 0.2 O 1.9 (SDC) powder preparation:

[0108] 1) Weigh a certain stoichiometric ratio (molar ratio of 4:1) of Ce(NO3)3·6H2O and Sm(NO3)3·6H2O and dissolve them in deionized water.

[0109] 2) Adding citric acid and ethylenediaminetetraacetic acid to the uniformly dissolved solution, the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5.

[0110] 3) After the solution is evenly mixed, slowly add ammonia water to adjust the pH to 6 while stirring continuously.

[0111] 4) Then, a stirring bar was added to warm water at 80° C. and stirring was continued until a light yellow, viscous, transparent wet gel was formed.

[0112] 5) The obtained wet gel was quickly transferred to a cup-shaped container and dried in an oven at 180° C. for 12 h to obtain a porous dry gel.

[0113] 6) The dry gel was then transferred to a muffle furnace and calcined at 900°C for 3 h to obtain SDC powder.

[0114] Ⅱ. Prepare the powder in step Ⅰ into cathode slurry, anode slurry and isolation layer slurry.

[0115] Preparation of cathode slurry: SFM powder, SDC powder and pinene alcohol were placed in a small cup-shaped container at a mass ratio of 65:35:150 and ground for 1 h until they were evenly mixed to form a viscous electrode slurry.

[0116] Preparation of anode slurry: LSCF powder, SDC powder and pinene alcohol were placed in a small cup-shaped container at a mass ratio of 65:35:150 and ground for 1 h until they were evenly mixed to form a viscous electrode slurry.

[0117] Preparation of isolation layer slurry: SDC powder and pinene alcohol were placed in a small cup-shaped container at a mass ratio of 1:1.5, and ground for 1 hour until they were evenly mixed to form an isolation layer slurry with viscosity.

[0118] III. Apply the isolation layer slurry in step 2) on one side of the solid electrolyte substrate by screen printing, and obtain the isolation layer after drying and calcining; then apply the cathode slurry on the isolation layer by screen printing, and dry to obtain the cathode; then apply the anode slurry on the other side of the solid electrolyte substrate by screen printing, and dry to form the anode; finally, calcine to obtain a complete solid oxide electrolyte.

[0119] Among them, the preparation of the solid electrolyte substrate: LSGM powder (purchased directly) is dry-pressed into an electrolyte green body at a pressure of 200 MPa, and then calcined at 1400°C for 4 hours to obtain a solid electrolyte substrate.

[0120] Specifically, the isolation layer slurry is evenly applied on one side of the electrolyte substrate by screen printing, dried in an oven at 100°C, and transferred to a muffle furnace for calcination at 1200°C for 5h. Subsequently, the prepared cathode slurry is evenly applied on the same side of the electrolyte substrate by screen printing and dried in an oven at 100°C. Take it out, and evenly apply the prepared anode slurry on the other side of the electrolyte substrate by screen printing, and dry it in an oven at 100°C. Take it out, transfer it to a muffle furnace and calcine it at 1100°C for 2h to obtain a complete solid oxide electrolytic cell.

[0121] IV. The cathode of the solid oxide electrolyte in step III is subjected to an impregnation modification treatment so that La is attached to the base layer of the cathode. 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles or CuO nanoparticles.

[0122] Preparation of impregnation solution:

[0123] Type I nitrate solution:

[0124] Dissolve Cu(NO3)2·3H2O in anhydrous ethanol to prepare 0.1 mol·L -1 of nitrate solution.

[0125] Type II nitrate solution:

[0126] 1) La(NO3)3·6H2O, Sr(NO3)2, Cr(NO3)3·9H2O, and Mn(NO3)2 in a certain stoichiometric ratio (molar ratio of 8:2:5:5) were mixed into a nitrate solution;

[0127] 2) Citrate and ethylenediaminetetraacetic acid are added to the above solution, and the molar ratio of total metal ions: ethylenediaminetetraacetic acid: citric acid is 1:1:1.5.

[0128] 3) Stir the prepared solution in a water bath at 80°C and slowly add a certain amount of ammonia water while controlling the pH at 6 to prepare 0.1 mol·L -1 of nitrate solution.

[0129] Electrode modification: The first type of nitrate solution or the second type of nitrate solution is dripped on the cathode side of the solid oxide electrolytic cell with a pipette, dried in an oven at 80°C, and then the cell is calcined in a muffle furnace at 600°C for 2 hours to obtain a modified electrode, with CuO nanoparticles or LSCM nanoparticles attached to the cathode. The attached CuO nanoparticles or LSCM nanoparticles account for 2wt% of the mass ratio of the cathode material.

[0130] Embodiment 3

[0131] Ⅰ. Preparation of Sr2Fe 1.5 Mo 0.5 O6(SFM) powder, La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0132] Sr2Fe 1.5 Mo 0.5 Preparation of O6(SFM) powder:

[0133] 1) Weigh Sr(NO3)2, Fe(NO3)3·9H2O and (NH4)6Mo7O in a certain stoichiometric ratio (molar ratio of 2:1.5:0.5). 24 4H2O was dissolved in deionized water.

[0134] 2) Adding citric acid and ethylenediaminetetraacetic acid to the uniformly dissolved solution, the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5.

[0135] 3) After the solution is evenly mixed, slowly add ammonia water to adjust the pH to 8 while stirring continuously.

[0136] 4) Then, a stirring bar was added to warm water at 80° C. and stirring was continued until a yellow-brown, viscous, transparent wet gel was formed.

[0137] 5) The obtained wet gel was quickly transferred to a cup-shaped container and dried in an oven at 160° C. for 7 h to obtain a porous dry gel.

[0138] 6) The dry gel was then transferred to a muffle furnace and calcined at 1050° C. for 5 h to obtain SFM powder.

[0139] La 0.7 Sr 0.3 Co 0.2 Fe 0.8 Preparation of O3(LSCF) powder:

[0140] 1) Weigh a certain stoichiometric ratio (molar ratio of 7:3:8:2) of La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O and Co(NO3)2·6H2O and dissolve them in deionized water.

[0141] 2) Adding citric acid and ethylenediaminetetraacetic acid to the uniformly dissolved solution, the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5.

[0142] 3) After the solution is evenly mixed, slowly add ammonia water to adjust the pH to 8 while stirring continuously.

[0143] 4) Then, a stirring bar was added to warm water at 80° C. and stirring was continued until a yellow-brown, viscous, transparent wet gel was formed.

[0144] 5) The obtained wet gel was quickly transferred to a cup-shaped container and dried in an oven at 160° C. for 7 h to obtain a porous dry gel.

[0145] 6) The dry gel was then transferred to a muffle furnace and calcined at 1050°C for 3 h to obtain LSCF powder.

[0146] Ce 0.8 Sm 0.2 O 1.9 (SDC) powder preparation:

[0147] 1) Weigh a certain stoichiometric ratio (molar ratio of 4:1) of Ce(NO3)3·6H2O and Sm(NO3)3·6H2O and dissolve them in deionized water.

[0148] 2) Adding citric acid and ethylenediaminetetraacetic acid to the uniformly dissolved solution, the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5.

[0149] 3) After the solution is evenly mixed, slowly add ammonia water to adjust the pH to 8 while stirring continuously.

[0150] 4) Then, a stirring bar was added to warm water at 80° C. and stirring was continued until a light yellow, viscous, transparent wet gel was formed.

[0151] 5) The obtained wet gel was quickly transferred to a cup-shaped container and dried in an oven at 180° C. for 12 h to obtain a porous dry gel.

[0152] 6) The dry gel was then transferred to a muffle furnace and calcined at 900°C for 3 h to obtain SDC powder.

[0153] Ⅱ. Prepare the powder in step Ⅰ into cathode slurry, anode slurry and isolation layer slurry.

[0154] Preparation of cathode slurry: SFM powder, SDC powder and pinene alcohol were placed in a small cup-shaped container at a mass ratio of 65:35:150 and ground for 1 h until they were evenly mixed to form a viscous electrode slurry.

[0155] Preparation of anode slurry: LSCF powder, SDC powder and pinene alcohol were placed in a small cup-shaped container at a mass ratio of 65:35:150 and ground for 1 h until they were evenly mixed to form a viscous electrode slurry.

[0156] Preparation of isolation layer slurry: SDC powder and pinene alcohol were placed in a small cup-shaped container at a mass ratio of 1:1.5, and ground for 1 hour until they were evenly mixed to form an isolation layer slurry with viscosity.

[0157] III. Apply the isolation layer slurry in step 2) on one side of the solid electrolyte substrate by screen printing, and obtain the isolation layer after drying and calcining; then apply the cathode slurry on the isolation layer by screen printing, and dry to obtain the cathode; then apply the anode slurry on the other side of the solid electrolyte substrate by screen printing, and dry to form the anode; finally, calcine to obtain a complete solid oxide electrolyte.

[0158] Among them, the preparation of the solid electrolyte substrate: LSGM powder (purchased directly) is dry-pressed into an electrolyte green body at a pressure of 200 MPa, and then calcined at 1400°C for 4 hours to obtain a solid electrolyte substrate.

[0159] Specifically, the isolation layer slurry is evenly applied on one side of the electrolyte substrate by screen printing, dried in an oven at 100°C, and transferred to a muffle furnace for calcination at 1200°C for 5h. Subsequently, the prepared cathode slurry is evenly applied on the same side of the electrolyte substrate by screen printing and dried in an oven at 100°C. Take it out, and evenly apply the prepared anode slurry on the other side of the electrolyte substrate by screen printing, and dry it in an oven at 100°C. Take it out, transfer it to a muffle furnace and calcine it at 1100°C for 2h to obtain a complete solid oxide electrolytic cell.

[0160] IV. The cathode of the solid oxide electrolyte in step III is subjected to an impregnation modification treatment so that La is attached to the base layer of the cathode. 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles or CuO nanoparticles.

[0161] Preparation of impregnation solution:

[0162] Type I nitrate solution:

[0163] Dissolve Cu(NO3)2·3H2O in anhydrous ethanol to prepare 0.1 mol·L -1 of nitrate solution.

[0164] Type II nitrate solution:

[0165] 1) La(NO3)3·6H2O, Sr(NO3)2, Cr(NO3)3·9H2O, and Mn(NO3)2 in a certain stoichiometric ratio (molar ratio of 8:2:5:5) were mixed into a nitrate solution;

[0166] 2) Citrate and ethylenediaminetetraacetic acid are added to the above solution, and the molar ratio of total metal ions: ethylenediaminetetraacetic acid: citric acid is 1:1:1.5.

[0167] 3) Stir the prepared solution in a water bath at 80°C and slowly add a certain amount of ammonia water while controlling the pH at 8 to prepare 0.1 mol·L -1 of nitrate solution.

[0168] Electrode modification: The first type of nitrate solution or the second type of nitrate solution is dripped on the cathode side of the solid oxide electrolytic cell with a pipette, dried in an oven at 80°C, and then the cell is calcined in a muffle furnace at 600°C for 2 hours to obtain a modified electrode, with CuO nanoparticles or LSCM nanoparticles attached to the cathode. The attached CuO nanoparticles or LSCM nanoparticles account for 8wt% of the mass ratio of the cathode material.

[0169] Comparative Example: The only difference from Example 1 is that the cathode is not modified by using the impregnation solution. Named SFM.

[0170] In order to verify the performance of the solid oxide electrolytic cell obtained in the present invention, the solid oxide electrolytic cell obtained in Experimental Example 1 is tested below.

[0171] (1) The chemical stability of the comparative SFM electrode, the Cu-SFM electrode obtained in Experimental Example 1, and the LSCM-SFM electrode materials was studied by X-ray diffraction. Figure 2 As shown, the diffraction peaks of the modified electrode material are consistent with those of the original SFM, and there is good chemical compatibility between SFM, SDC and LSGM.

[0172] (2) The surface microstructures of the original SFM electrode, Cu-SFM, and LSCM-SFM electrode materials were characterized by scanning electron microscopy (SEM). Figure 3As shown, (a) is a scanning electron microscope image of the surface of the original SFM (comparative example) electrode material, (b) is a scanning electron microscope image of the surface of the Cu-SFM electrode material, and (c) is a scanning electron microscope image of the surface of the LSCM-SFM electrode material. A large number of nanoparticles were observed to be deposited on the SFM surface. The number of nanoparticles on the LSCM-infiltrated electrode is less than that on the CuO-infiltrated electrode. These nanoparticles cover the surface of the SFM, effectively increasing the specific surface area of ​​the electrode and generating additional active sites.

[0173] Preparation of symmetrical cells: In order to test the impedance change of electrode materials in CO2 atmosphere, symmetrical cells were prepared and tested. The specific preparation method is as follows: The prepared SDC isolation layer slurry is symmetrically applied on both sides of the electrolyte substrate by screen printing, dried in an oven at 100°C, and transferred to a muffle furnace for calcination at 1200°C for 5h. Subsequently, the prepared SFM cathode slurry is evenly applied on both sides of the electrolyte substrate by screen printing and dried in an oven at 100°C. Take it out, transfer it to a muffle furnace and calcine it at 1100°C for 2h to obtain a complete symmetrical cell. Use a pipette to drop the impregnation solution on both sides of the symmetrical cell, dry it at 80°C in an oven, and then calcine the cell in a muffle furnace at 600°C for 2h to obtain the modified symmetrical cell. The one modified with the first type of nitrate solution is named Cu-SFM, and the one modified with the second type of nitrate solution is named LSCM-SFM. Similarly, the SFM with unmodified electrodes on both sides of the symmetrical cell is used as a comparison. The three symmetrical batteries mentioned above were tested, and the EIS curves in pure CO2 atmosphere were as follows: Figure 4 The results show that the ohmic resistance and polarization resistance of Cu-SFM and LSCM-SFM electrodes are reduced, and the polarization resistance values ​​are 14.1 and 16.8 Ω cm, respectively. 2 , than SFM (22.1Ωcm 2 ) are about 36.2% and 24.0% lower.

[0174] The two solid oxide electrolytic cells obtained in Experimental Example 1 and the solid oxide electrolytic cell obtained in Comparative Example were tested using an electrochemical workstation (CHI-660E). The test results are shown in Figure 2. Figure 5 and Figure 6 As shown:

[0175] EIS curve under open circuit voltage ( Figure 5 ) The results show that the ohmic resistance and polarization resistance of the electrode impregnated with nanoparticles are reduced. Compared with SFM (2.60Ωcm 2 ), the CuO-modified battery has the smallest polarization resistance (1.61Ωcm 2 ), performance improvement over LSCM (2.25Ωcm 2 ) is more significant.

[0176] IV Curve( Figure 6 ) The results showed that the current density of the electrode impregnated with nanoparticles increased. The current density of the solid oxide electrolysis cell based on Cu-SFM and LSCM-SFM cathodes at 1.8 V was 510 and 405 mA cm, respectively. -2 , which is higher than that of the solid oxide electrolyzer based on SFM cathode (383 mA cm -2 ).

Claims

1. A solid oxide electrolysis cell for high temperature electrolysis of carbon dioxide, characterized in that: It includes a solid electrolyte substrate, a separation layer located on one side of the solid electrolyte substrate, a cathode located on the separation layer, and an anode located on the other side of the solid electrolyte substrate; The solid electrolyte substrate material is La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O3(LSGM), isolation layer material is Ce 0.8 Sm 0.2 O 1.9 (SDC), cathode material is Sr2Fe 1.5 Mo 0.5 O6(SFM) and Ce 0.8 Sm 0.2 O 1.9 (SDC) composed of a composite, and La is attached to the cathode material 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles or CuO nanoparticles; the anode material is La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) and Ce 0.8 Sm 0.2 O 1.9 (SDC) composed of a complex.

2. The solid oxide electrolysis cell for high temperature electrolysis of carbon dioxide according to claim 1, characterized in that: The CuO nanoparticles or La 0.8 Sr 0.2 Cr 0.5 Mn 0.5 The attachment amount of O3 (LSCM) nanoparticles is 2wt%-8wt% of the mass ratio of the nanoparticles to the cathode material.

3. A method for preparing a solid oxide electrolytic cell for high-temperature electrolysis of carbon dioxide as claimed in claim 1, characterized in that: The following steps are included: Ⅰ. Preparation of Sr2Fe 1.5 Mo 0.5 O6(SFM) powder, La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder; II. preparing the powder in step I into cathode slurry, anode slurry and separator slurry; III. Apply the isolation layer slurry in step II to one side of the solid electrolyte substrate by screen printing, dry and calcine to obtain an isolation layer; then apply the cathode slurry to the isolation layer by screen printing, and dry to form a cathode; then apply the anode slurry to the other side of the solid electrolyte substrate by screen printing, and dry to form an anode; finally, calcine to obtain a complete solid oxide electrolytic cell; IV. The cathode of the solid oxide electrolytic cell in step III is subjected to an impregnation modification treatment to allow La to adhere to the cathode material. 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles or CuO nanoparticles.

4. The method for preparing a solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide according to claim 3, Features: In step Ⅰ, Sr2Fe 1.5 Mo 0.5 O6(SFM) powder was prepared by the following method, 1) Sr(NO3)2, Fe(NO3)3·9H2O and (NH4)6Mo7O 24 4H2O is dissolved in deionized water as a raw material to form a nitrate solution; 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, wherein the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5; 3) adding an aqueous ammonia solution to the solution in step 2) to adjust the pH to 6-8; 4) stirring the solution in step 3) in a heated water bath to obtain a wet gel; 5) drying the wet gel to obtain a dry gel; 6) Calcine the dry gel to obtain Sr2Fe 1.5 Mo 0.5 O6(SFM) powder.

5. The method for preparing a solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide according to claim 3, characterized in that: In step Ⅰ, La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) powder was prepared by the following method: 1) dissolving La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O and Co(NO3)2·6H2O as raw materials in deionized water to form a nitrate solution; 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, wherein the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5; 3) adding an aqueous ammonia solution to the solution in step 2) to adjust the pH to 6-8; 4) stirring the solution in step 3) in a heated water bath to obtain a wet gel; 5) drying the wet gel to obtain a dry gel; 6) Calcine the dry gel to obtain La 0.7 Sr 0.3 Co 0.2 Fe 0.8 O3(LSCF) powder.

6. The method for preparing a solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide according to claim 3, Features: In step Ⅰ, Ce 0.8 Sm 0.2 O 1.9 (SDC) powder was prepared by the following method, 1) dissolving Ce(NO3)3·6H2O and Sm(NO3)3·6H2O as raw materials in deionized water to form a nitrate solution; 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, wherein the molar ratio of the total amount of metal ions to the ethylenediaminetetraacetic acid and citric acid is 1:1:1.5; 3) adding an aqueous ammonia solution to the solution in step 2) to adjust the pH to 6-8; 4) stirring the solution in step 3) in a heated water bath to obtain a wet gel; 5) drying the wet gel to obtain a dry gel; 6) Calcine the dry gel to obtain Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

7. The method for preparing a solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide according to claim 3, characterized in that: SFM powder, SDC powder and pinene alcohol are placed in a cup-shaped container at a mass ratio of 65:35:150, and ground until they are uniformly mixed to form a cathode slurry with viscosity; LSCF powder, SDC powder and pine oil are placed in a cup-shaped container in a mass ratio of 65:35:150, and ground until they are evenly mixed to form a viscous anode slurry; SDC powder and pine oil are placed in a cup-shaped container in a mass ratio of 1:1.5, and ground until they are evenly mixed to form a viscous isolation layer slurry.

8. The method for preparing a solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide according to claim 3, characterized in that: In step IV, the impregnation solution is prepared as follows, Dissolve Cu(NO3)2·3H2O in anhydrous ethanol to prepare Cu(NO3)2·3H2O with a concentration of 0.1 mol·L -1 The first type of nitrate solution.

9. The method for preparing a solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide according to claim 3, characterized in that: In step IV, the impregnation solution is prepared as follows, 1) Dissolve La(NO3)3·6H2O, Sr(NO3)2, Cr(NO3)3·9H2O, and Mn(NO3)2 in anhydrous ethanol to form a nitrate solution. 2) adding citrate and ethylenediaminetetraacetic acid to the above solution, with the molar ratio of total metal ions: ethylenediaminetetraacetic acid: citric acid being 1:1:1.5; 3) The prepared solution was heated in a water bath and stirred, and ammonia water was added to control the pH value of the solution to 6-8 to prepare La 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) concentration is 0.1 mol·L -1 The second type of nitrate solution.

10. The method for preparing a solid oxide electrolysis cell for high-temperature electrolysis of carbon dioxide according to claim 8 or 9, characterized in that: In step IV, the first type of nitrate solution or the second type of nitrate solution is dripped onto the cathode material, dried, and then calcined, so that CuO nanoparticles or La nanoparticles are attached to the cathode material. 0.8 Sr 0.2 Cr 0.5 Mn 0.5 O3 (LSCM) nanoparticles.

Citation Information

Patent Citations

  • Cathode material of solid oxide fuel cell in A omission type perovskite structure

    CN101847725A

  • Novel cathode and electrolyte materials for solid oxide fuel cells and ion transport membranes

    CN101918337A

  • High temperature solid oxide electrolytic bath with double-layer composite interlayer

    CN105734607A

  • Electrode material of quasi-symmetric solid oxide electrolytic cell as well as preparation method and application thereof

    CN111621807A

Cited By

  • LSCF material based on gel-assisted solid-phase reaction method and preparation method

    CN120463247A

  • Solid oxide electrolytic cell sheet anode material as well as preparation method and application thereof

    CN120505660A